Power Of Resources And Capacity Of Community Adaptation In Forest Fire Disaster - Okka, Oktavianus; Pandjaitan, Nurmala K; Sumarti, Titik (Sodality: Jurnal Sosiologi Pedesaan, 2019)
The widespread forest fires in South Sumatra were disastrous for the community around the forest area. However, this condition is beneficial to sonor underage activities. The government policy number 6 of 2016 that prohibit forests and/or land limits people's access to exploit the potential of forests as a source of income and food sources. The community’s adaptation to new condition/regulation is not easy because of the community’s dependent to forest. The purpose of this study is to look at forest as resources and the community's adaptive capacity. This study uses qualitative methods supported by quantitative data. The study indicated that there is a decrease of forest as the main source of livelihood. Sonor rice can no longer be produced, other forest plants have been greatly reduced because the forest has changed into a plantation. Rubber production is reduced due to heat from fires. The adaptive capacity of the community is classified as lacking because although there have been repeated fires there has been no change or new way that the community has done to overcome the lack of food resources. Linkages with outside parties have little impact on the growth of new economic opportunities. The lack of effective leadership role is one of the main causes. The resiliency of the Perigi community is only in Stability.